MENGUKUR EVALUASI PENERAPAN SAK EMKM PADA KINERJA KEUANGAN MIKRO - Afriani, Raden Irna; Widyaningsih, Ika Utami (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2023)
This research evaluates the success of implementing Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in improving financial performance, with a focus on the case study of Rumah Crafts, a typical Banten clothing manufacturing industry. Even though Indonesia has a wealth of valuable culture, Micro, Small and Medium Enterprises (MSMEs) often do not realize the importance of preparing financial reports according to standards. The research results show that the recording system at the Craft House is simple and does not include financial reporting elements in accordance with SAK EMKM. The Financial Position Report, Profit and Loss Report and Notes to Financial Reports have not been prepared according to standards, indicating a lack of understanding. The research highlights the importance of improving understanding and implementation of SAK EMKM to support the growth of MSMEs in Indonesia. Outreach and training efforts are needed to change perceptions and increase awareness of business actors, especially MSMEs, regarding the benefits of financial accounting standards in managing their businesses.